The Crack Propagation Trend Analysis in Ceramic Rolling Element Bearing considering Initial Crack Angle and Contact Load Effect - Zhe Yuan; Bohan Wang; Chao Liu; Zhan Wang; Xiaochen Zhang; Yu Zhang (Shock and Vibration)
Silicon nitride ceramic bearings are widely used for their excellent performance. However, due to their special manufacturing method, cracks will occur on ceramic ball surface, and this initial surface crack will propagate under the action of cyclic stress, which will lead to material spalling. This will greatly limit its service life in practical applications, especially under heavy load at high speed. Therefore, it is necessary to study the surface crack propagation of silicon nitride ceramic bearings. In this paper, the effect of initial crack angle and contact load on crack growth is analysed by the finite element method (FEM). A three-dimensional finite element model of a silicon nitride bearing ball containing an initial crack is created by the FEM. The cracks are initially classified based on the angle between the crack and the bearing ball surface, and the location of the most dangerous load for each type of crack is known by theoretical analysis. The stress intensity factors (SIFs) are calculated for the crack front to investigate the effect of load position on crack growth. Subsequently, the SIFs are calculated for each type of crack angle subdivided again to investigate the effect of crack angle on crack propagation.